Physicochemical and mechanical properties of a new cold-set emulsion gel system and the effect of quinoa protein fortification - Ingrassia, Romina (2022)
A new approach for soft and self-sustainable oil-in-water emulsion gel systems (EGs) preparation based on a formulation with olive oil, sodium alginate, citric acid, and calcium chloride, and the combination of high-speed homogenization and gelation induction by glucono-δ-lactone addition is presented. Also, the effect of EG protein fortification by the incorporation of quinoa concentrate (QC) and quinoa flour on the physicochemical and mechanical properties of these EGs upon storage at 4 °C was investigated. Despite soft and self-sustainable EGs (10 g/kg and 20 g/kg alginate, respectively) showed higher oil droplet size increment with total biopolymer concentration, these systems presented remarkable stability during 28 days. All fortified EGs showed higher fluid retention capacity (>99%), L*, a*, and lower b* values. After one day, EGs presented pHs ranging 4.1–4.3, and longer storage times promoted an increased acidity, to a less extent for QC-fortified-EGs. Lipid oxidation degree also increased during storage (from 30 to 150 μmol/L malonaldehyde), with no significant effects upon protein fortification. Protein fortification promoted higher gel strength in all self-sustainable EGs (from 3.5 N to almost 7 N), and especially after 14 days for soft-EGs. These EGs can be used in the food industry as fat replacers to formulate healthier products.